Low Impact Felling Distance and Allowable Number of Felled Trees in TPTI System - Ahmad Budiaman; Adita Agung Pradata (Jurnal Manajemen Hutan Tropika, 2013)
Indonesian Selective Cutting and Planting System (TPTI) is a silvicultural system of production natural forests management conducted in Indonesia. TPTI implementation has resulted in damage to the residual stands and threatened the existence of production natural forests in Indonesia. This study assessed the damage level of the residual stands of commercial species due to low cutting intensity (0.77 trees ha-1), calculated low damages cutting distance, and determined the number of trees ha-1 which could be harvested sustainably. Dynamic sample plots with a circular shape with a radius of 2 times the height of felled trees were used in this study, and the number of sample plots was 29 plots with an average area of 1.3 ha. In the sample plots, the tree species, total height, diameter at breast height (dbh), and number of commercial trees ≥ 10 cm dbh were measured before and after cutting. The results showed that the damage level of residual stands caused by the low cutting intensity was 2.1%, where the damages included broken stems, splitted stems, and injured stems, leaning trees, fallen trees, broken crowns and broken buttresses. The low cutting intensity had damaged 7 commercial tree species with the diameter ≥ 10 cm. The study recommends sustainable cutting on TPTI with a distance of > 1.5 times the height of felled trees and the number of trees ha-1 that may be sustainably felled is no more than 5 trees ha-1.